Assessment of Sarcopenia as a Predictor of Poor Outcomes After Esophagectomy in Elderly Patients With Esophageal Cancer. Issue 6 (June 2018) - Nakashima, Yuichiro; Saeki, Hiroshi; Nakanishi, Ryota; Sugiyama, Masahiko; Kurashige, Junji; Oki, Eiji; Maehara, Yoshihiko
Abstract : Objective: The objective of the study was to elucidate the impact of sarcopenia in elderly patients with esophageal cancer on postoperative complications and long-term survival after surgery for esophageal cancer. Summary Background Data: Sarcopenia, defined as loss of skeletal muscle mass with age, has been identified as a poor prognostic factor for malignancies. This retrospective study investigated the effect of sarcopenia on surgical outcomes among young and elderly patients with esophageal cancer. Methods: Data were collected for 341 consecutive patients who underwent esophagectomy for esophageal cancer. Patients were assigned to 2 groups according to age (younger than 65 years and 65 years or older) and the presence of sarcopenia. Results: Sarcopenia was present in 170 of 341 patients (49.9%) with esophageal cancer and in 74 of 166 elderly patients (44.6%). The incidence of anastomotic leak and in-hospital death was significantly higher in the elderly sarcopenia group than in the elderly nonsarcopenia group (31.5% vs 15.2%, P = 0.015, 6.8 vs 0.0%, P = 0.037, respectively), and the overall survival rate in patients with sarcopenia correlated with a significantly poor prognosis in the elderly group ( P < 0.001). Multivariate analysis revealed that sarcopenia was a risk factor for an anastomotic leak ( P = 0.034) and was an unfavorable prognostic factor for survival ( P < 0.001). Those correlations between sarcopenia and surgical outcomes were not observed in the young group. Conclusions: Sarcopenia and worse surgical outcomes were significantly associated patients with in esophageal cancer aged 65 years and older but not in those younger than 65 years.